Kritik Sanad Hadis (Studi Sunan Ibnu Majah, Kitab Az-Zuhud) - Zaenal Arifin (Hikmah: Journal of Islamic Studies, 2018)
There are three elements of the validity of the method in determining the authenticity of a Hadith: it’s connection by isnad, credibility of the narrator, syużūż and ‘illah. The focus of the study in this article is to examine the isnad hadith narrated by Ibn Majah through companions ‘Abd ar-Rahman (Abu Hurayrah) found in Sunan Ibn Majah, Kitab al-Zuhud, hadith number 4102. it’s done by takhreej of hadith and i’tibar, it recorded by researchers the quality of the narrators and its connectioned, and the possibility of checking by syużūż and ‘illah. Finally seen that entire hadith is created by śiqat and its isnaad muttaşil (connected) from the Prophet Muhammad to the last creature and Ibn Majah as mukharrij al-hadith, and not found the presence of syużūż or ‘illah, so that have the best quality that can enter the category of hadith is hasan li ghairih. Keywords: Isnad Criticism, Hadith, Kitab al-Zuhud There are three elements of the validity of the method in determining the authenticity of a Hadith: it’s connection by isnad, credibility of the narrator, syużūż and ‘illah. The focus of the study in this article is to examine the isnad hadith narrated by Ibn Majah through companions ‘Abd ar-Rahman (Abu Hurayrah) found in Sunan Ibn Majah, Kitab al-Zuhud, hadith number 4102. it’s done by takhreej of hadith and i’tibar, it recorded by researchers the quality of the narrators and its connectioned, and the possibility of checking by syużūż and ‘illah. Finally seen that entire hadith is created by śiqat and its isnaad muttaşil (connected) from the Prophet Muhammad to the last creature and Ibn Majah as mukharrij al-hadith, and not found the presence of syużūż or ‘illah, so that have the best quality that can enter the category of hadith is hasan li ghairih. Keywords: Isnad Criticism, Hadith, Kitab al-Zuhud